Indonesian Sign Language (SIBI) Vocabulary Learning Media Design Based on Augmented Reality for Hearing-Impaired Children - Anggraeni, Martianda; Sarinastiti, Widi; Wati, Setiyo (Faculty of Engineering, Universitas Brawijaya, 2019)
The lack of mastery of spoken and written vocabulary makes hearing-impaired children have poor vocabulary designations. A case study in a kindergarten school for hearing-impaired children in Surabaya, the students are taught to understand vocabulary through media recognition with original objects, artificial objects, and through images. For media recognition through images usually use media in the flashcards form. The rapid development of Information and Communication Technologies (ICT) such as the Augmented Reality (AR) should also be utilized to support the learning media for hearing-impaired children. In this study an application based on AR technology has been integrated with flashcards as a learning tool for children with hearing impairment in learning the vocabulary of the Indonesian sign language (SIBI) In designing the learning media, we use Luther's version of multimedia development method, include concept, design, material collecting, assembly, testing, and distribution. Based on the test results, it would be concluded that the AR application system would run well as evidenced by the buttons on this AR application 100% running according to its function. Markers on the flashcard 97% are detected by the system and would be integrated with appropriate video displays. As for this AR application that runs offline in which all assets and videos are stored in the application database installed on the device, the RAM and processor capacity is very influential on the success and speed of detection of markers and access to display video. So it is recommended to use a device with a minimum of 1.5 GB RAM and a 1.4GHz Quad-core processor. With this AR application, we hope hearing-impaired children become more interested in learning and increasing their vocabulary independently.